Structural Model of System Information for Management Innovation Ruminant-Slaughterhouse - Muhammad Syarif, Hartawan; Maya, Dewi Dyah Maharani; Erly, Krisnanik (2020)
In the digital age, data and information such as performance of Ruminant-Slaughterhouse, both true and false, could spreads faster than ever. The same information technology that provides access to data across the globe very possible can abet the warping of truth and normalization of lies. The truth, untruth and information technology, including how social media manipulates behavior, technologies such as deep fakes spread misinformation, including the bias inherent in algorithms. The aim of the study is formulating a structural model for the Information System Management Innovation Ruminant-Slaughterhouse by understanding the interaction and contextual 3 elements (objectives, constraints, and benchmarks). This model is needed as the basis for the operational policy of the 2020-2024 technology research and innovation program, specially for sustainability of management Ruminant-Slaughterhouse. The research methodology includes secondary data collection based on literature study and expert consultation, and analysis using ISM. The results show that the key goal is to increase the true digital leadership of Manager Ruminant-Slaughterhouse; Provide Vision and Empower Ruminant-Slaughterhouse Users and Workers, and Give up control and Empower Ruminant-Slaughterhouse Users & Workers. The key constraint are: Online Deception of slaughtered diseased animal, Online deception of processed meat, conflict between Users. The benchmarks for the success of the objectives are: fake news goes viral decreasing, and social media manipulates human behavior decreasing.